PedsCases - A Learning Module for Kawasaki Disease for Medical Students - Chris Gerdung; Melanie Lewis; Claire LeBlanc; Janet Ellsworth (Association of American Medical Colleges, 2010)
Abstract This resource is a learning module designed to provide medical students with an approach to the diagnosis and treatment of Kawasaki disease in the pediatric population. The module includes a case that centers around an 11-month-old child who presents with a history of fever and rash. Using this initial information, the case involves multiple-choice questions to review the differential diagnosis of Kawasaki disease as well as the clinical findings needed to diagnose this disease. In addition, the case discusses the potential complications of the disease as well as the treatment of Kawasaki disease and the necessary follow-up once the diagnosis is made. The learning module also includes a podcast that supplements the material presented in the case. The podcast explains the clinical importance and pathology of Kawasaki disease, as well as the diagnostic criteria, current treatment regime, and follow-up necessary for Kawasaki disease. A script for the podcast is also included. This resource is a part of PedsCases, a comprehensive web-based educational series that focuses on the core objectives of undergraduate pediatric education with extensive student involvement. PedsCases was created for and by medical students to provide an opportunity for active self-directed learning in pediatrics. The learning modalities available include questions, flash card-type quizzes, multistep clinical cases, and podcasts.